2D stepping drive for hyperspectral systems. (22nd May 2015) - Endrödy, Csaba; Mehner, Hannes; Grewe, Adrian; Sinzinger, Stefan; Hoffmann, Martin
Abstract: We present the design, fabrication and characterization of a compact 2D stepping microdrive for pinhole array positioning. The miniaturized solution enables a highly integrated compact hyperspectral imaging system. Based on the geometry of the pinhole array, an inch-worm drive with electrostatic actuators was designed resulting in a compact (1 cm 2 ) positioning system featuring a step size of about 15  µ m in a 170  µ m displacement range. The high payload (20 mg) as required for the pinhole array and the compact system design exceed the known electrostatic inch-worm-based microdrives.